(untitled) (Scientific journal of the Fergana State University, 2025)
Based on archival sources, the article analyzes information about the construction of settlements for the army during the reign of Emir Nasrullah, who founded the regular army in the Emirate of Bukhara, the order of deployment, organization of troop movements, and the situation of the barracks of the emirate’s army during the protectorate of Bukhara, the Russian Empire.